Mulheres nas águas: Um estudo sobre relações de gênero na pesca - Cavalcanti, Diego Rocha Medeiros (2010)
This dissertation seeks to show the role of fisherwomen and seafood collectors among coastal communities in the area of the extractive reserve of Acaú-Goiana, located in the border of the States of Paraíba and Pernambuco. I analyse how women have entered the spheres of work and politics and show the importance of their actions for the social reproduction of their communities. Despite the increasing participation of women in the activities of fishing and gathering in mangroves and in the sea, fishing is still regarded as a typically masculine activity by many authors. A vision grounded in a bipolar model of perceiving the world, opposing sea-land, men and women, leaded to a non-perception of women as producers and agents and produced a myth of invisibility of women within the fishing universe. I argue that local gender relations are changing quickly, and women s activities are, now a days, very important in the household budget. The diminishing importance of superstitions and taboos related to women's condition is also an important cultural marker of this small, but meaningful change. The increasing participation of women in political and institutional instances also legitimizes such change in the role of women in fishing communities of the Goiana estuary. In fact, the fight for the conservation unit (Marine Extractive Reserve) is doubtless an action of local women, based on their Unions but also on interpersonal networks. The increasing number of women s Unions reflects the political context, specially the economic and social importance given by the Brazilian government to the artisanal fishermen and fisherwomen in the last years.